INVENTARISASI ASET DAERAH KABUPATEN KEPULAUAN MERANTI OLEH BADAN PENDAPATAN PENGELOLAAN KEUANGAN ASET DAERAH KABUPATEN KEPULAUAN MERANTI - Nurul Jannatul Putri; Mimin Sundari Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Assets have a very strategic role in supporting the implementation of the main tasks and functions of local government. The availability of assets that suit the needs will directly improve the performance of local government organizations. There is also a formulation of the problem in the research is How is the inventory of regional assets at the Regional Asset Management Revenue Agency of the Meranti Islands Regency? What are the obstacles in the inventory ofregional assets at the Regional Asset Management Revenue Agency of the Meranti Islands Regency?. This study aims to find out how to inventory regional assets at the Regional Asset Management Revenue Agency of the Meranti Islands Regency and to find out the obstacles inthe regional asset inventory of Meranti Islands Regency. In this study the authors used aqualitative research type. Based on th eresults of the research and discussion that was carried out in the previous chapter related to the inventory of regional assets of the Meranti IslandsRegency by the Meranti Islands Regency Regional Asset Management Revenue Agency, theconclusion was drawn that the activity of inventorying regional assets of Meranti IslandsRegency by the Meranti Islands Regency Regional Asset Management Revenue Agency foundthat asset inventory activities have not been properly implemented and there are obstaclesrelated to the Meranti Islands Regencyregional asset inventory by the Regional AssetManagement Revenue Agency Meranti Islands Regency, namely human resources and lowperformance. Keywords: Inventory,Asset, Financial Management